Correlation between Clear Air Turbulence and Temperature Gradients At standard isobaric levels - BHASKARARAO , NS; SADAGOPAN, A (MAUSAM, 1968)
The forecasting offices which render service to turbo-prop and jet, aircraft have to indicate the probable area of Clear Air Turbulence (CAT} and If possible the Inter Sity of the CAT which is likely to be encountered Results by the aircraft. Forecasting of CAT from synoptic data is beset with many problems which have been discussed in Section 2 of this paper. There is, however, an apparent correlation between the occurrence of CAT and the increase of thermal gradient. This was statistically tested in the tested in the case of all flights for which post-fight reports were available at the Main Meteorological Office, Santacruz for the year 1964. The results of the test are discussed in this paper. Briefly the results show that the method based on thermal gradients is a good guide for delineating probable areas of CAT occurrence but the method was not very sensitive for discriminating different intensities of CAT. The method has a good potentiality to be used as a forecasting tool.